2008
DOI: 10.1111/j.1746-1049.2008.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Employment Effects of Innovations: Microeconometric Evidence From Taiwan

Abstract: This paper aims to identify the effects of innovation on employment and labor composition in Taiwan. Using a new and detailed firm-level data set, the empirical results determine that innovations, measured by R&D investments or patent counts, have a positive impact on employment. Both of the estimated employment effects of product and process innovations are overall significantly positive. Although the effects of process innovations differ between high and low R&D-intensive industries, the process innovation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…Turning to the analysis of the relationship between innovation and employment considering potential differences among different sectors, previous literature has very rarely split the empirical analysis according to sectoral belonging. Yang and Lin (2008) On the whole -although the microeconometric evidence is not conclusive about the possible employment impact of innovation -the majority of recent investigations provide evidence of a positive link, especially when R&D and/or product innovation are adopted as proxies of technological change and when high-tech sectors (manufacturing and services) are considered. A feebler evidence of a labor-saving impact of process innovation is also detected in some studies, especially when low-tech manufacturing is exploited.…”
Section: Previous Microeconometric Evidencementioning
confidence: 99%
“…Turning to the analysis of the relationship between innovation and employment considering potential differences among different sectors, previous literature has very rarely split the empirical analysis according to sectoral belonging. Yang and Lin (2008) On the whole -although the microeconometric evidence is not conclusive about the possible employment impact of innovation -the majority of recent investigations provide evidence of a positive link, especially when R&D and/or product innovation are adopted as proxies of technological change and when high-tech sectors (manufacturing and services) are considered. A feebler evidence of a labor-saving impact of process innovation is also detected in some studies, especially when low-tech manufacturing is exploited.…”
Section: Previous Microeconometric Evidencementioning
confidence: 99%
“…The final issue is that some studies report disproportionately large numbers of estimates compared to the rest. For example, four studies (Berndt et al ., ; van Reenen, ; Yang and Lin, ; Lachenmaier and Rottmann, ) account for 43% of the total estimates in the evidence pool. Even though the HM takes account of between‐ and within‐study dependence, the sheer number of estimates reported by such studies may dominate the informational content of the evidence base and the meta‐regression estimates.…”
Section: Why Hierarchical Meta‐regression?mentioning
confidence: 99%
“…4 Wage premium trends for postgraduate education 12 Some studies have found that there were skill-biased technological changes and led to a higher demand for higher educated and skilled labor in Taiwan in late 1990 to early 2000s, e.g. Tang and Tseng (2004) and Yang and Lin (2008). and quality.…”
Section: Effects Of Postgraduate Education Expansion On Individual Prmentioning
confidence: 99%